Renal artery stenosis and ambulatory blood pressure monitoring: A case report and review of the literature. Issue 4 (25th October 2017) - Reeves, Ryan R.; Walters, Daniel; Mahmud, Ehtisham
Abstract: Renal artery stenosis (RAS) is a prevalent cause of secondary hypertension. Elderly patients with atherosclerosis and young women with fibromuscular dysplasia (FMD) are particularly at risk. Blood pressure screening is often key to this diagnosis, although the reliability of clinical screening has been questioned, and ambulatory blood pressure monitoring (ABPM) likely offers superior ability to diagnose poorly controlled hypertension. In patients with RAS, medical management should be the primary means of therapy; however, in a select group of these patients, renal revascularization may be considered, and has been shown to reduce blood pressure and stabilize chronic kidney disease. In this report, we present a patient diagnosed with RAS due to FMD, found to have significant hypertension via ABPM, and treated successfully with percutaneous renal artery angioplasty; importantly, continuous 24‐hr ambulatory monitoring after pressure gradient guided renal angioplasty confirmed reduction in blood pressure.